Household Solid Waste Management Strategy in Danau Teluk Sub-District, Jambi City - Dea Rifka Irawan; Hutwan Syarifuddin; Sukmal Fakhri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Danau Teluk Sub-District is one of the sub-districts in Jambi City. The waste production produced by Danau Teluk Sub-District based on DLH Jambi City data in 2020 reached 8,793.99 kg/day with a population of 12,563 people. In Danau Teluk Sub-District, the production of managed waste reached 71.05% and unmanaged waste reached 28.95%. Compared to other sub-districts, the percentage of managed waste is the lowest and the percentage of unmanaged waste is the highest. This research is conducted on influencing factors using distribution frequency and multiple linear regression, community and government involvement using distribution frequency and chi-square, and determining strategic priorities in household solid waste management using SWOT. Based on the results of the study, there are two factors that influence the management of household solid waste, namely behaviour and knowledge of local regulations, there are two factors that relate to the management of household solid waste, namely implementation and supervision, then the strategic are to carry out waste reduction starting from the source by reducing the use of goods that produce waste and providing data on waste management that is easily accessible to the public such as through social media, websites, television advertisements, bulletin boards, etc.